TO THE QUESTION OF EVOLUTION OF „FRIEND" AND „ENEMY" IMAGE IN THE POSTWAR BELARUS AND UKRAINE, 1945 - 1953 - Капітонова, Т.; Крисенко, О.; Сташкевич, О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The paper presents an analytical review of the scientific research project implemented by Belarusian-Ukrainian team with the help of Geschichtswekstatt Europа – the program of German Foundation „Erinnerung, Verantwortung, Zukunft” of the Institute of applied history with the co-operation with the Viadrin European University. The purpose and topicality of this research is analysed. The problems of construction of mental memory structures based on individual experiences and feelings experienced by participants of historical events are examined. The conclusions about the paradoxical nature of the co-existence in the experience of the collective consciousness of "friendship" and threats from the government are made.